Associação entre cronotipo, food craving e ganho ponderal na gestação - Teixeira, Gabriela Pereira (2019)
Introduction: Some studies in the literature have suggested that obesity and worse feeding behavior are associated with eveningness, that is, the individual preference to perform activities at later times of the day. However, the relationship between chronotype and food craving, which is defined as an intense desire to eat a specific food that is difficult to resist, has been insufficient explored by studies and, in the best of our knowlegment, never before performed with pregnant women. Objective: This study investigated the association between chronotype, food craving in pregnant women and weight gain in early pregnancy (between 12 and 20 gestational weeks). Methods: A total of 245 women, with age between 18 and 45 years (median = 27 years old), attended in the public health service in the city of Uberlandia, Minas Gerais, Brazil, was evaluated. Chronotype was assessed by mid-sleep time. Food Craving was assessed by Food Craving Questionnaire Trait and State validated for Brazilian population. The weight and higher was measured. Generalizes linear models were used to determine the association between variables analyzed. Results: Evening types presented a higher anticipation of relief from negative states and feeling as a result of eating as an usual behaviour compared to morning (β = 0.180; p = 0.013) and non-evening types (β = 0.150; p = 0.028); less intense desire to eat as a sporadic behaviour compared to morning (β = 0.188; p = 0.012) and non-evening types (β = -0.184; p = 0.009); and less anticipation of positive reinforcement that may result from eating as a sporadic behaviour than non-evening types (β = -0.152; p = 0.022). We also found a significant association between chronotype and anticipation of relief from negative states and feeling as a result of eating as an usual behaviour (β = 0.053; p = 0.004); anticipation of positive reinforcement that may result from eating as an usual behaviour (β = 0.041; p = 0.013); weight gain during early gestational period (β = 0.923; p = 0.024); and, intense desire to eat as a sporadic behaviour (β = -0.04; p = 0.045). Conclusion: Evening chronotype was associate to food craving trait and those pregnant women who chronotype values are indicative of eveningness presented higher weight gain in early pregnancy.